Transcriptome and functional analysis in a Drosophila model of NGLY1 deficiency provides insight into therapeutic approaches. (15th January 2018) - Owings, Katie G; Lowry, Joshua B; Bi, Yiling; Might, Matthew; Chow, Clement Y
Abstract: Autosomal recessive loss-of-function mutations in N-glycanase 1 ( NGLY1 ) cause NGLY1 deficiency, the only known human disease of deglycosylation. Patients present with developmental delay, movement disorder, seizures, liver dysfunction and alacrima. NGLY1 is a conserved cytoplasmic component of the Endoplasmic Reticulum Associated Degradation (ERAD) pathway. ERAD clears misfolded proteins from the ER lumen. However, it is unclear how loss of NGLY1 function impacts ERAD and other cellular processes and results in the constellation of problems associated with NGLY1 deficiency. To understand how loss of NGLY1 contributes to disease, we developed a Drosophila model of NGLY1 deficiency. Loss of NGLY1 function resulted in developmental delay and lethality. We used RNAseq to determine which processes are misregulated in the absence of NGLY1 . Transcriptome analysis showed no evidence of ER stress upon NGLY1 knockdown. However, loss of NGLY1 resulted in a strong signature of NRF1 dysfunction among downregulated genes, as evidenced by an enrichment of genes encoding proteasome components and proteins involved in oxidation–reduction. A number of transcriptome changes also suggested potential therapeutic interventions, including dysregulation of GlcNAc synthesis and upregulation of the heat shock response. We show that increasing the function of both pathways rescues lethality. Together, transcriptome analysis in a Drosophila model of NGLY1 deficiency provides insight into potential therapeutic approaches.